Altered gut microbiota in temporal lobe epilepsy with anxiety disorders - Wei, Shouchao; Mai, Yingren; Hu, Li; Zheng, Ruxing; Zheng, Dongming; Chen, Wenrong; Cai, Yan; Wang, Junjun (Frontiers in Microbiology, 2023)
Introduction: Patients with epilepsy are particularly vulnerable to the negative effects of anxiety disorders, which became more pressing under the current COVID-19 pandemic. In particular, temporal lobe epilepsy with anxiety disorders (TLEA) have attracted more attention in epilepsy research. The link between intestinal dysbiosis and with TLEA has not been established yet. To gain deeper insight into the link between gut microbiota dysbiosis and factors affecting TLEA, the composition of the gut microbiome, including bacteria and fungi have been examined. Method: The gut microbiota from 51 temporal lobe epilepsy patients has been subjected to sequencing targeting 16S rDNA (Illumina MiSeq) and from 45 temporal lobe epilepsy patients targeting ITS-1 region (through pyrosequencing). A differential analysis has been conducted on the gut microbiota from phylum to genus level. Results: TLEA patients' gut bacteria and fungal microbiota exhibited distinct characteristics and diversity as evidenced by high-throughput sequencing (HTS). TLEA patients showed higher abundances of Escherichia-Shigella (genus), Enterobacterales (order), Enterobacteriaceae (family), Proteobacteria (phylum), Gammaproteobacteria (class), and lower abundance of Clostridia (class), Firmicutes, Lachnospiraceae (family), Lachnospirales (order), and Ruminococcus (genus). Among fungi, Saccharomycetales fam. incertae sedis (family), Saccharomycetales (order), Saccharomycetes (class), and Ascomycota (phylum) were significantly more abundant in TLEA patients than in those with temporal lobe epilepsy but without anxiety. Adoption and perception of seizure control significantly affected TLEA bacterial community structures, while yearly hospitalization frequency affected fungal community structures in TLEA patients. Conclusion: Our study revealed here validated the gut microbiota dysbiosis of TLEA. And the pioneering study of bacterial and fungal microbiota profiles will help in understanding the course of TLEA and drive us toward preventing TLEA gut microbiota dysbiosis.